The Effect of Strategic Leadership and Motivation Towards Satisfaction and its Impact on Employee Performance - Otong Karyono, M. Yusuf A. Samad (International Journal of Advanced Science and Technology, 2020)
Each organization either public or business, leadership and motivation factors are important aspects in increasing satisfaction and employee performance. Therefore, this research empirically studied leadership, work motivation, satisfaction, and performance factors either descriptively or verificatively. The research method used in this research was quantitative with survey technique. The samples of this research were staffs of Transportation, Communication, and Information Department either civil servant or honorary status. Samples were selected through proportional random sampling. Data sources in this research were 145 staffs. The analysis technique used in this research was path analysis with the assistance of SPSS 20.0 Version Program. The descriptive research results show that motivation is higher if compared to leadership, satisfaction, and performance. The verificative research results prove that leadership and motivation partially and simultaneously influence satisfaction and satisfaction is proven to have effect on performance.